UTKIR HOSHIMOV — THE ARTIST OF LIFE AND TRUTH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article discusses the place of the Uzbek writer O‘tkir Hoshimov in our literature and his creative views. It analyzes the extent to which human psychology, realism, and spiritual values are reflected in the writer’s works. Furthermore, the significance of his literary creativity for contemporary literary processes and spiritual life is highlighted.